Effect of Total Water Percentage on Circadian Blood Pressure Variation in Prehypertensive Patients - Ahmet Cimbek; Ahmet Özderya (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Circadian changes in blood pressure are a key factor in determining cardiovascular risk. A normal dipper pattern shows a decrease in blood pressure at night, whereas a non-dipper pattern shows a smaller decrease at night. Changes in the distribution of bodily fluids may affect how blood vessels work and how blood pressure changes over the course of a day. This study aimed to examine the correlation between total body water percentage and circadian blood pressure patterns in individuals classified as prehypertensive. This retrospective cross-sectional study comprised 300 prehypertensive individuals who underwent 24-hour ambulatory blood pressure monitoring and body composition measurement via bioelectrical impedance. Patients were classified into two groups according to the magnitude of nocturnal blood pressure decline: dipper and non-dipper. Clinical, echocardiographic, and hydration characteristics were compared between the dipper and non-dipper groups. In the study population, 124 patients exhibited a dipper pattern, while 176 displayed a non-dipper pattern. Non-dipper patients exhibited a markedly reduced total body water percentage in comparison to dipper persons. Echocardiographic measures, such as interventricular septal thickness and left ventricular end-diastolic diameter, were markedly elevated in the non-dipper cohort. In multivariable logistic regression analysis, total body water percentage persisted as an independent predictor of non-dipper blood pressure pattern. A lower percentage of total body water is linked to a non-dipper blood pressure pattern in individuals who are prehypertensive. These findings indicate that modifications in body fluid content may play a role in circadian blood pressure dysregulation and heightened cardiovascular risk.